Effects of stretch-shortening cycle fatigue protocol on lower limb asymmetry and muscle soreness in judo athletes - Lima Kons, R.; Bet da Rosa Orssatto, L.; Sakugawa, R. L.; Nelson da Silva Junior, J.; Diefenthaeler, F.; Detanico, D. (Sports Biomechanics, 2023)
This study aimed to analyse unilateral countermovement jumps (CMJ) performance and muscle soreness in lower limbs, as well as to compare lower limb asymmetry over 48h after a stretch-shortening cycle (SSC) fatigue protocol. Fourteen judo athletes performed unilateral CMJ on each leg before, and after the 5th and 10th sets over 24h and 48h of an SSC-fatigue protocol. The SSC protocol reduced CMJ performance after the 5th set and 10th sets, especially in the weaker limb (p < 0.05), but returned to the baseline values after 24h. Asymmetry increased for peak force, peak power, and mean power after the 5th set compared to the baseline (p < 0.05) and remained higher for peak force after the 10th set (p = 0.019), returning to the baseline values after 24h (p < 0.05). Soreness increased for the lower body at post, 24h, and 48h compared to the baseline (p < 0.05). In conclusion, a fatiguing SSC protocol can result in increased bilateral asymmetries in judo athletes, but after 24h and 48h of the protocol the bilateral asymmetry returned to the baseline values, with only muscle soreness still elevated.